2016
DOI: 10.1002/ps.4455
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics analysis of Callosobruchus chinensis larvae under hypoxia, hypoxia/hypercapnia and normoxia

Abstract: The findings show that bean weevil has high tolerance to hypoxia or even hypoxia/hypercapnia at biologically achievable levels and provide more direct evidence for stored product insect mechanism regulation under hypoxia stress, especially free fatty acid regulation by hypercapnia but not by hypoxia. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Tyrosine (or 4-hydroxyphenylalanine) is an aromatic amino acid that is used by cells to synthesize proteins. Tyrosine is also an antioxidant that can scavenge free radicals and contribute to reduce oxidative damage caused by hypoxic stress [66]. Lysine is an α-amino acid, and an essential amino acid for protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine (or 4-hydroxyphenylalanine) is an aromatic amino acid that is used by cells to synthesize proteins. Tyrosine is also an antioxidant that can scavenge free radicals and contribute to reduce oxidative damage caused by hypoxic stress [66]. Lysine is an α-amino acid, and an essential amino acid for protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…MAs generally involve O 2 , CO 2 , NO, and O 3 . Insect tolerance to hypoxia and hypercapnia critically affects insect control (Cui et al., 2017). O 2 is critical for the survival of aerobic life.…”
Section: Modified Atmosphere Gases Commonly Used For Pest Control Andmentioning
confidence: 99%
“…However, contents of energy substances, including polysaccharides, soluble proteins, and lipids, decreased in a dose- and time-dependent manner in response to CO 2 in larvae of S. paniceum and L. serricorne (Cao et al., 2016a) and adult S. paniceum (Cao et al., 2016b) and O. surinamensis (Cao et al., 2015b). In bean weevil ( Callosobruchus chinensis Linnaeus), Cui et al. (2017) reported that the levels of carbohydrates, amino acids, and organic acids increased, whereas those of free fatty acids decreased in response to hypoxia.…”
Section: Changes In Energy/nutrient Sources Under Modified Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have paid more attention to this pest control strategies of MA, but little is known about this mechanism of action (Mohapatra et al, 2015). According to our previous research, bean weevil shows high adaptability to hypoxia even hypoxia/hypercapnia (Cui et al, 2017). To further reveal bean weevil hypoxia and hypoxia/hypercapnia tolerance mechanism, we used NextSeq500 RNA-Seq to investigate the differences in gene expression profiles among 4th adzuki bean weevil larvae under hypoxia, hypoxia/hypercapnia and normoxia.…”
Section: Introductionmentioning
confidence: 99%